A Study on the Symbolic Language Used in Certain Depictions Portraying Suleyman the Magnificent's Last Military Campaign - (:unkn) unknown (ISTANBUL 29 MAYIS UNIV & ISAM, 2018)
This study is an analysis of the symbolic language observed in a number of miniatures depicting various events from the last years of Suleyman the Magnificent's reign (926-974/1520-1566) until the beginning of that of Selim II (974-982/1566-1574). I will focus especially on the tree stump motif seen in the miniature depicting the event of deploying Suleyman the Magnificent's corpse, attributed to Nakkas Osman (d. after 1001/1592), found in Feridun Ahmed Bey's (d. 991/1583) Nuzhet-i esraru'l-ahyar der-ahbar-i Sefer-i Sigetvar (Pleasures of the Secrets of Auspicious Men from the News of the Szigetvar Campaign, 976/1569), and in the senility portrait of Suleyman the Magnificent attributed to Nigari (d. 980/1572). The tree stump is recognized as a cult motif that heralds the genealogical continuity of religious and political authority. I will argue that in the above mentioned miniatures, it represents the continuity of the dynasty, and the transfer of dynastic power. The tree stump motif and the depictions of nature and of animals in these miniatures were selected to complement the theme depicted and added into the composition to enhance the narrative. There seems to be an obvious interaction among the painter, the poet and the author reflected in the document.
Keywords: Nakkas Osman; Nigari; tree stump with shoot; the Ottoman dynasty; survival of the state; accession to the throne event; Ottoman miniatures; allegory